Ni-based bimetallic multifunctional catalyst as well as preparation method and application thereof
By using Ni-M-Al2O3 catalyst, the catalyst is prepared by efficient in-situ desolution method, which solves the problems of short service life, complex preparation and high cost of existing catalysts, and achieves efficient and specific hydrogenation reaction of dimethyl maleate, which improves the selectivity of dimethyl succinate.
Patent Information
- Application Number
- CN202411904837.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing catalysts have a short service life in the hydrogenation reaction of dimethyl maleate, complex preparation process, high cost, and easy loss of active components, resulting in poor catalyst circulation stability.
Ni-M-Al2O3 is used as a catalyst to synthesize Ni-M-Al hydrotalcite precursor oxide with a layered porous structure, and prepare Ni-M bimetallic multifunctional catalyst by efficient in situ desolution. The multifunctionality of the catalyst and multi-center synergistic catalysis are used to achieve highly selective preparation of dimethyl succinate.
It improves the service life of the catalyst, simplifies the preparation process, reduces costs, enhances the uniformity and dispersion of the active phase distribution, avoids the migration or loss of active metal sites, and achieves efficient and specific hydrogenation activity and selectivity.
Smart Images

Figure CN119701963A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysis, and specifically relates to a Ni-based bimetallic multifunctional catalyst and a preparation method and application thereof. Background Art
[0002] Dimethyl succinate (DMS), also known as dimethyl succinate, is a colorless or light yellow liquid substance at room temperature. As an important chemical intermediate, it is widely used in food, spices, medicine, coatings, rubber, plastics and other industries for synthesizing light stabilizers, high-grade coatings, bactericides, and pharmaceutical intermediates. The traditional production process of dimethyl succinate is prepared by esterification reaction using succinic acid and methanol as raw materials and concentrated sulfuric acid as catalyst. However, this process of esterification catalyzed by concentrated sulfuric acid is highly corrosive to the device, has many side reactions, low production capacity, difficult product separation, and the byproduct dimethyl sulfate is highly toxic, seriously polluting the environment, and cannot meet the development needs of modern green chemistry. At present, another environmentally friendly synthesis process of dimethyl succinate is obtained by hydrogenation reaction using dimethyl maleate (DMM) and hydrogen as raw materials and precious metal or non-precious metal catalysts. This catalytic process avoids the disadvantages of corrosion of equipment by concentrated sulfuric acid in traditional processes.
[0003] In the hydrogenation reaction of dimethyl maleate, the noble metal catalyst can realize the rapid hydrogenation of unsaturated bonds under mild conditions, mainly based on Pd-based or Pt-based catalysts, for example, the Chinese patent with publication number CN103464153A discloses a hydrogenation catalyst for producing dimethyl succinate and its preparation method, the catalyst is a resin-based spherical activated carbon with a microporous structure as a carrier, first loaded with Pd by a liquid phase precipitation method, and then loaded with WO3, prepared by washing, drying and roasting, the catalyst preparation process is complicated and the cost is relatively high. And because the noble metals are expensive and environmentally unfriendly, many researchers have shifted their research focus to the development of non-noble metal catalysts. Nickel-based catalysts are the most economical and widely used catalytic materials in the hydrogenation reaction of non-noble metal catalysts, mainly based on Raney Ni and supported Ni-based catalysts. Patent publication number CN115253923A reports a system and method for preparing dimethyl succinate by liquid phase hydrogenation of dimethyl maleate. The catalyst is a supported Ni-based catalyst with carbon or alumina as a carrier. Since the interaction between the metal and the carrier is weak, Ni particles are easily aggregated and lost after reduction, resulting in poor catalyst cycle stability.
[0004] In view of this, the above-mentioned prior art has the disadvantages of short catalyst service life, complex preparation process, high cost, easy loss of active components, etc., and its metal carrier interaction is poor. These methods often lead to uneven distribution of active phases and low dispersion. Under high temperature or liquid phase conditions, active metal sites are easy to migrate or lose, resulting in catalyst deactivation. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a low-cost, simple to prepare, efficient, highly specific Ni-based bimetallic multifunctional catalyst for catalyzing the hydrogenation of dimethyl maleate to dimethyl succinate and its preparation method and application. The present invention first synthesizes a Ni-M-Al hydrotalcite precursor oxide (M is one to three of Cr, Mn, Fe, Co or Cu) with a layered porous structure, and then prepares the Ni-M bimetallic multifunctional catalyst by an efficient in-situ precipitation method, making full use of the multifunctionality of the catalyst and the multi-center synergistic catalysis, including basic sites, acidic sites and bimetallic hydrogenation active sites, and through the synergistic catalytic effect of the bimetallic basic sites and the strong metal carrier interaction, the target product dimethyl succinate is prepared with high selectivity under mild conditions.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] On the one hand, the present invention provides a Ni-based bimetallic multifunctional catalyst, the general formula of which is Ni-M-Al2O3, wherein M represents one to three of Cr, Mn, Fe, Co or Cu; Al2O3 is used as a carrier, Ni and M are metal active components, the microstructure of the carrier Al2O3 exists in an amorphous form, and a partial lamellar skeleton structure of hydrotalcite is maintained at the nanoscale, and nanoparticles of the metal active components Ni and M are uniformly distributed inside or on the inner surface of the Al2O3 skeleton, that is, Ni-M alloy nanoparticles are uniformly grown on the lamellar pore walls of the Al2O3 nanosheets.
[0008] Furthermore, in terms of mass percentage, the contents of the components in the Ni-M-Al2O3 are as follows: Ni is 20-50%, M is 10-30%, and the total amount of Ni+M is 20-60%, with the remainder being Al2O3.
[0009] Furthermore, the specific surface area of the Ni-M-Al2O3 is 140 to 180 m 2 ·g -1 The average pore size is 5-15 nm and the pore volume is 0.25-0.65 cm 3 ·g -1 , the Ni-M alloy particle size is 3.5~9.5nm.
[0010] Another aspect of the present invention provides a method for preparing the Ni-based bimetallic multifunctional catalyst as described above, comprising the following steps:
[0011] (1) dissolving nickel salt, M salt and aluminum salt in deionized water to prepare a metal salt solution; dissolving NaOH and Na2CO3 in deionized water to prepare a NaOH-Na2CO3 mixed alkaline solution;
[0012] (2) adding NaOH-Na2CO3 mixed alkali solution and metal salt solution to deionized water simultaneously for coprecipitation titration;
[0013] (3) After the co-precipitation is completed, the precipitation solution is aged to obtain a precursor precipitate;
[0014] (4) washing, drying, and calcining the precursor precipitate to obtain metal oxide NiMAl-LDHs;
[0015] (5) The metal oxide NiMAl-LDHs is reduced to obtain the catalyst Ni-M-Al2O3.
[0016] Furthermore, in the step (1), the nickel salt, M salt and aluminum salt are solutions of their nitrates, acetates or other soluble salts; the molar fraction ratio of the nickel salt, M salt and aluminum salt is 1-3:1-3:1, and the molar fraction ratio of the nickel salt + M salt and aluminum salt is 2-4:1; the total concentration of the metal salt solution is 0.3-1.0 mol / L, and the volume of the metal salt solution is 75-250 mL; the concentration of NaOH in the NaOH-Na2CO3 mixed alkaline solution is 1-1.8 mol / L, the concentration of Na2CO3 is 0.3-0.6 mol / L, and the molar ratio of NaOH to Na2CO3 is 0.3-0.38:1; the volume of the NaOH-Na2CO3 mixed alkaline solution is 50-200 mL.
[0017] Furthermore, the volume of deionized water in step (2) is 75 to 250 mL; during the coprecipitation titration process, the volume flow ratio of the metal salt solution to the NaOH-Na2CO3 mixed alkaline solution is controlled to be 0.75 to 2.5:0.5 to 2, the titration duration is 1.3 to 6 hours, the pH value of the mixed solution is maintained at 9 to 11, and the operating temperature is 50 to 100°C.
[0018] Furthermore, the aging temperature in step (3) is 20-30°C and the time is 12-36 hours; the washing liquid used for washing in step (4) is deionized water, ethanol or ethanol / water mixed solution, and the drying temperature is 70-200°C.
[0019] Furthermore, the calcination conditions in step (4) are as follows: the calcination atmosphere is static air, flowing air or flowing nitrogen atmosphere, the heating rate is 0.5-10°C / min, the calcination temperature is 350-600°C, and the calcination time is 3-6h.
[0020] Furthermore, the reduction conditions in step (5) are as follows: the reducing gas is hydrogen or a mixture of hydrogen and nitrogen, wherein the volume flow ratio of hydrogen to nitrogen is 1:0-3, the reduction temperature is 400-600° C., and the reduction time is 3-5 hours.
[0021] Another aspect of the present invention also provides the use of the Ni-based bimetallic multifunctional catalyst as described above for hydrogenating dimethyl maleate to produce dimethyl succinate.
[0022] The hydrogenation activity of dimethyl maleate of the Ni-based bimetallic multifunctional catalyst of the present invention can be evaluated by the following method: the catalyst activity is investigated in a 100mL stainless steel high-pressure hydrogenation reactor. In the experiment, 3-15g dimethyl maleate, 0.06-0.3g Ni-M-Al2O3 catalyst of 20-60 mesh and 27-70mL anhydrous methanol solvent are loaded into the high-pressure reactor. After sealing, the reaction system is first flushed with N2 and H2 for 5 times each, and then pressurized to the required pressure with pure H2. The reaction temperature and pressure are set at 50-120°C and 1-5MPa, and the reaction is continued for 20min-3h at a stirring rate of 200-600r / min. The product after the reaction is analyzed by a gas chromatograph (Aglient 7890A), and the content of each component is detected by a hydrogen ion flame detector (FID), and the capillary column is HP-5.
[0023] In the process of hydrogenating dimethyl maleate to dimethyl succinate, mixed hydrogenation of various functional groups such as C=C, C=O, -CO-OR is involved. Especially under high temperature and pressure, -COO- and C=O are more easily activated, and the reaction rate of hydrogenation to produce other by-products will be accelerated. After removing two equal amounts of methanol in the first stage, dimethyl succinate (DMS) can be hydrogenated to γ-butyrolactone (GBL). Then, GBL can be further hydrogenated to 1,4-butanediol (BDO) in the second stage. In addition, GBL can also be converted into tetrahydrofuran (THF) through the hydrogenolysis process. In addition, BDO can also be dehydrated to form THF. Therefore, the hydrogenation reaction can produce products such as GBL, BDO and THF. Then, in order to achieve complete conversion of dimethyl maleate and high selectivity of dimethyl succinate, it is required that the catalyst used can activate C=C and inhibit C=O hydrogenation and -COO- hydrogenolysis. The working principle of the hydrogenation of dimethyl maleate of the Ni-based bimetallic multifunctional catalyst of the present invention is: layered double hydroxides (LDHs), as an ordered two-dimensional anionic clay, provide highly dispersed and stable metal centers due to their multifunctionality, multi-center synergistic catalysis, controllable chemical composition and laminar lattice restriction properties. The design concept of the present invention is to provide a Ni-M-Al2O3 ternary catalyst, which is composed of active components Ni, M (one to three of Fe, Co, Cu, Cr, and Mn) and Al2O3. It has a more regular pore distribution and a larger specific surface area than the supported nickel-based catalyst prepared by the traditional method. After the introduction of the second metal site component M, the alloying of Ni and M reduces the d-band center of Ni, which is beneficial to the desorption of H*. M can form an electronic effect with the active metal Ni, weakening the electron density of Ni after reduction, which is beneficial to the reduction of Ni, reducing the reduction temperature of the active component oxide, and improving the low-temperature activity of the catalyst. The Ni-M synergistic bimetallic effect rapidly hydrogenates the reaction from C=C to CC; and after high-temperature calcination, the alkaline active sites of the LDHs catalyst will be exposed in large quantities, and the alkalinity will be enhanced, which can adsorb and occupy the -COO- site. Through the synergistic catalytic effect of the Ni-M bimetallic alkaline sites and the strong metal-support interaction, the formation of deep hydrogenation products under high temperature and high pressure is inhibited, so that the catalyst shows excellent low-temperature activity, high high-temperature specificity and hydrogenation activity and selectivity in the dimethyl maleate reaction after reduction activation. Dimethyl maleate can be almost completely converted at a higher feedstock space velocity, and a higher selectivity for dimethyl succinate is obtained, with almost no by-products. For example, under the conditions of a reaction temperature of 50-100°C and a reaction pressure of 2MPa, the conversion rate of dimethyl maleate can reach 100%, and the selectivity of dimethyl succinate is 100%.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) The Ni-based bimetallic multifunctional catalyst of the present invention has a long service life, a simple preparation process, a low cost, a strong metal-carrier interaction, a uniform distribution of the active phase, a high degree of dispersion, and the active metal sites are not easy to migrate or lose under high temperature or liquid phase conditions.
[0026] 2) The present invention prepares a highly active Ni-M bimetallic multifunctional catalyst by an efficient in-situ desolvation method. After reduction, the active metals Ni and M are dissolved from the skeleton structure to the catalyst surface to form a Ni-M alloy. The metals have a strong synergistic effect. The presence of M species increases the adsorption of active H species on the catalyst surface. The bimetallic synergistic effect promotes the active metal Ni 0 The site quickly hydrogenates the reaction from C=C to CC, and the alkaline active sites of the LDHs catalyst after high-temperature calcination can inhibit the adsorption between -COO- and the active components, effectively reducing the loss of active components. The three bimetallic alkaline sites work synergistically to effectively improve the hydrogenation activity of the catalyst and extend the service life of the catalyst.
[0027] 3) The Ni-based bimetallic multifunctional catalyst of the present invention has a low activation temperature in the hydrogenation reaction, good low-temperature activity, and high specificity. The preferred low-temperature reaction conditions (50-100°C) can effectively inhibit the high-temperature polymerization of C4 unsaturated substances in the raw materials during the hydrogenation reaction, avoid the formation of oligomers, and ensure the reaction stability of the catalyst.
[0028] 4) In the preparation method of the present invention, the trivalent cations on the LDHs layer plate make the layer plate skeleton positively charged, and the anions with opposite charges between the layers are balanced with it, so that the entire crystal is electrically neutral. The divalent metal ions and trivalent metal ions with hydrogenation activity are introduced into the LDHs layer plate. Under the combined influence of the lowest lattice energy and the positioning effect of atoms in the crystal, these metal active components are highly dispersed in the LDHs precursor, and the introduction of the second metal M can form an electronic effect with the active metal, and can effectively control the size of Ni particles, inhibit the migration and agglomeration of Ni nanoparticles, greatly reduce the reduction temperature of the active component oxide, and improve the low-temperature activity and stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the X-ray diffraction spectrum of the sample after calcination and reduction of the precursor of Example 3 of the present invention and the sample after reduction of Comparative Example 1;
[0030] Figure 2 The N2 adsorption-desorption curve (left) and pore size distribution (right) of Example 6 of the present invention after calcination;
[0031] Figure 3 It is the H2-programmed temperature reduction diagram of Comparative Example 1 and Example 3 of the present invention. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0033] Example 1
[0034] (1) 7.3 g of nickel nitrate hexahydrate (0.025 mol), 7.3 g of cobalt nitrate hexahydrate (0.025 mol) and 9.4 g of aluminum nitrate nonahydrate (0.025 mol) were weighed and dissolved in 150 mL of deionized water, and stirred at a stirring rate of 800 r / min for 1 h to obtain a metal salt solution (the total concentration of the metal salt solution was 0.5 mol / L, and the molar fraction ratio of the nickel salt, the cobalt salt and the aluminum salt was 1:1:1); 6 g of NaOH and 4.8gNa2CO3 were dissolved in 150mL deionized water, stirred at a stirring rate of 800r / min for 1.5h to mix evenly, and a NaOH-Na2CO3 mixed alkaline solution (nNa2CO3:nNaOH=0.3:1) was obtained; the temperature of the 150mL deionized water bottom liquid was raised to 50°C, and stirred at a stirring rate of 540r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkaline solution was controlled to be 1:1 for coprecipitation titration, and the pH value of the mixed solution was maintained at 9, and the titration was completed in 1.5 hours. After the precipitation was completed, the precipitation solution was stirred at 30°C at a stirring rate of 550r / min for 24 hours for aging to obtain a precursor precipitate.
[0035] (2) Wash the precursor precipitate with deionized water for 6 times until it is neutral; place it in an oven at 100°C for 12 hours; transfer it to a muffle furnace and calcine it at 350°C in static air for 6 hours at a heating rate of 0.5°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni1Co1Al-LDHs.
[0036] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:3, the metal oxide Ni1Co1Al-LDHs was reduced by heating the temperature from room temperature to 550°C for 3 hours, and then taken out after cooling to room temperature to obtain catalyst 1, named Ni1-Co1-Al2O3. The mass percentage of Ni in the obtained catalyst is 23.3%, and the mass percentage of Co is 23.4%.
[0037] (4) Catalyst evaluation conditions: 3 g of dimethyl maleate, 0.06 g of 30-mesh Ni1-Co1-Al2O3 catalyst and 27 mL of anhydrous methanol solvent were added to a 100 mL stainless steel high-pressure hydrogenation reactor. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 2 MPa with pure H2. The reaction temperature and pressure were set at 50 °C and 2 MPa, and the reaction was continued at a stirring rate of 600 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 min and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 1.
[0038] Table 1 Evaluation results of catalyst 1
[0039] Catalyst 1 Operation time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni1-Co1-Al2O3]]> 40 100 100
[0040] Example 2
[0041] (1) 8.7 g of nickel nitrate hexahydrate (0.03 mol), 4.4 g of cobalt nitrate hexahydrate (0.015 mol), 4.3 g of manganese nitrate hexahydrate (0.015 mol) and 5.6 g of aluminum nitrate nonahydrate (0.015 mol) were weighed and dissolved in 190 mL of deionized water, and stirred at a stirring rate of 550 r / min for 50 min to obtain a metal salt solution (the total concentration of the metal salt solution was 0.4 mol / L, and the molar fraction ratio of the nickel salt, cobalt salt, manganese salt and aluminum salt was 2:1:1:1); 6.8 g of NaOH and 5.4 g of Na2CO3 was dissolved in 170mL of deionized water, and stirred at a stirring rate of 550r / min for 50min to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.3:1); the temperature of the 190mL deionized water bottom liquid was raised to 60°C, and stirred at a stirring rate of 560r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 1.9:1.7 for coprecipitation titration, and the pH value of the mixed solution was maintained at 10, and the titration was completed in 1.6 hours. After the precipitation was completed, the precipitation solution was stirred at 30°C at a stirring rate of 660r / min for 12 hours for aging to obtain a precursor precipitate.
[0042] (2) Wash the precursor precipitate with deionized water for 4 times until it is neutral; place it in an oven at 95°C for 12 hours; transfer it to a muffle furnace and calcine it at 480°C in flowing air for 4 hours at a heating rate of 5°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni2Co1Mn1Al-LDHs.
[0043] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:1, the metal oxide Ni2Co1Mn1Al-LDHs was reduced from room temperature to 400°C for 5 hours, and then taken out after cooling to room temperature to obtain catalyst 2, named Ni2-Co1-Mn1-Al2O3. The mass percentage of Ni in the obtained catalyst is 29.6%, the mass percentage of Co is 14.8%, and the mass percentage of Mn is 13.8%.
[0044] (4) Catalyst evaluation conditions: 5 g of dimethyl maleate was added to a 100 mL stainless steel high-pressure hydrogenation reactor, 0.1 g of Ni2-Co1-Mn1-Al2O3 catalyst and 45 mL of anhydrous methanol solvent were screened at 30 mesh. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 1 MPa with pure H2. The reaction temperature and pressure were set at 70 °C and 1 MPa, and the reaction was continued at a stirring rate of 600 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 min and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 2.
[0045] Table 2 Evaluation results of catalyst 2
[0046] Catalyst 2 Operation time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni2-Co1-Mn1-Al2O3]]> 60 100 100
[0047] Example 3
[0048] (1) Weigh 10.9 g of nickel nitrate hexahydrate (0.0375 mol), 5.5 g of cobalt nitrate hexahydrate (0.01875 mol) and 7.0 g of aluminum nitrate nonahydrate (0.01875 mol) respectively, dissolve them in 200 mL of deionized water, stir at a stirring rate of 500 r / min for 40 min to obtain a metal salt solution (the total concentration of the metal salt solution is 0.50 mol / L, and the molar fraction ratio of the nickel salt, cobalt salt and aluminum salt is 2:1:1); weigh 6 g of NaOH and 4.8 g of Na2CO3 was dissolved in 150mL of deionized water, and stirred at a stirring rate of 500r / min for 40min to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.3:1); the temperature of the 200mL deionized water bottom liquid was raised to 75°C, and stirred at a stirring rate of 600r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 2:1.5 for coprecipitation titration, and the pH value of the mixed solution was maintained at 11, and the titration was completed in 2.8 hours. After the precipitation was completed, the precipitation solution was stirred at 25°C at a stirring rate of 550r / min for 36 hours for aging to obtain a precursor precipitate.
[0049] (2) Wash the precursor precipitate with deionized water for 5 times until it is neutral; place it in an oven at 90°C for 12 hours; transfer it to a muffle furnace and calcine it at 500°C in static air for 4 hours at a heating rate of 8°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni2Co1Al-LDHs.
[0050] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:2, the metal oxide Ni2Co1Al-LDHs was reduced from room temperature to 600°C for 3 hours, and then taken out after cooling to room temperature to obtain catalyst 3, named Ni2-Co1-Al2O3. The mass percentage of Ni in the obtained catalyst is 36.1%, and the mass percentage of Co is 18.3%.
[0051] (4) Catalyst evaluation conditions: 10 g of dimethyl maleate, 0.2 g of Ni2-Co1-Al2O3 catalyst and 70 mL of anhydrous methanol solvent were added to a 100 mL stainless steel high-pressure hydrogenation reactor. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 2 MPa with pure H2. The reaction temperature and pressure were set at 100 °C and 2 MPa, and the reaction was continued at a stirring rate of 500 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 min and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 3.
[0052] Table 3 Evaluation results of catalyst 3
[0053] Catalyst 3 Operation time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni2-Co1-Al2O3]]> 30 100 100
[0054] Example 4
[0055] (1) 7.3 g of nickel nitrate hexahydrate (0.025 mol), 10.1 g of ferric nitrate nonahydrate (0.025 mol) and 9.4 g of aluminum nitrate nonahydrate (0.025 mol) were weighed and dissolved in 250 mL of deionized water, and stirred at a stirring rate of 600 r / min for 30 min to obtain a metal salt solution (the total concentration of the metal salt solution was 0.3 mol / L, and the molar fraction ratio of the nickel salt, the iron salt and the aluminum salt was 1:1:1); 14.4 g of NaOH and 12.7 g of Na2CO3 was dissolved in 200mL of deionized water, and stirred at a stirring rate of 600r / min for 30min to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.33:1); the temperature of the 250mL deionized water bottom liquid was raised to 75°C, and stirred at a stirring rate of 540r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 2.5:2 for coprecipitation titration, and the pH value of the mixed solution was maintained at 10, and the titration was completed in 1.3 hours. After the precipitation was completed, the precipitation solution was stirred at 30°C at a stirring rate of 660r / min for 12 hours for aging to obtain a precursor precipitate.
[0056] (2) Wash the precursor precipitate with deionized water for 4 times until it becomes neutral; place it in an oven at 70°C for 12 hours; transfer it to a muffle furnace and calcine it at 450°C in flowing air for 5 hours at a heating rate of 1°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni1Fe1Al-LDHs.
[0057] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:2.5, the metal oxide Ni1Fe1Al-LDHs was reduced by heating the temperature from room temperature to 550°C for 3 hours, and then taken out after cooling to room temperature to obtain catalyst 4, named Ni1-Fe1-Al2O3. The mass percentage of Ni in the obtained catalyst was 23.3%, and the mass percentage of Fe was 22.5%.
[0058] (4) Catalyst evaluation conditions: 3 g of dimethyl maleate was added to a 100 mL stainless steel high-pressure hydrogenation reactor, 0.06 g of Ni1-Fe1-Al2O3 catalyst with a 30 mesh screen and 27 mL of anhydrous methanol solvent. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 2 MPa with pure H2. The reaction temperature and pressure were set at 50 °C and 2 MPa, and the reaction was continued at a stirring rate of 600 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 min and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 4.
[0059] Table 4 Evaluation results of catalyst 4
[0060] Catalyst 4 Operation time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni1-Fe1-Al2O3]]> 80 100 100
[0061] Example 5
[0062] (1) 8.7 g of nickel nitrate hexahydrate (0.03 mol), 6.1 g of ferric nitrate nonahydrate (0.015 mol), 6.0 g of chromium nitrate nonahydrate (0.015 mol) and 5.6 g of aluminum nitrate nonahydrate (0.015 mol) were weighed and dissolved in 200 mL of deionized water, and stirred at a stirring rate of 550 r / min for 35 min to obtain a metal salt solution (the total concentration of the metal salt solution was 0.375 mol / L, and the molar fraction ratio of the nickel salt, iron salt, chromium salt and aluminum salt was 2:1:1:1); 8.8 g of NaOH and 9.0 g of Na2CO3 was dissolved in 170mL of deionized water, and stirred at a stirring rate of 550r / min for 35min to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.38:1); the temperature of the 200mL deionized water bottom liquid was raised to 85°C, and stirred at a stirring rate of 560r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 2:1.7 for coprecipitation titration, and the pH value of the mixed solution was maintained at 9, and the titration was completed in 2.6 hours. After the precipitation was completed, the precipitation solution was stirred at 20°C at a stirring rate of 500r / min for 36 hours for aging to obtain a precursor precipitate.
[0063] (2) Wash the precursor precipitate with deionized water for 5 times until it is neutral; place it in an oven and dry it at 150°C for 12 hours; transfer it to a muffle furnace and calcine it at 480°C in flowing air for 4 hours at a heating rate of 5°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni2Fe1Cr1Al-LDHs.
[0064] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:1.5, the metal oxide Ni2Fe1Cr1Al-LDHs was reduced from room temperature to 400°C for 3 hours, and then taken out after cooling to room temperature to obtain catalyst 5, named Ni2-Fe1-Cr1-Al2O3. The mass percentage of Ni in the obtained catalyst is 24.7%, the mass percentage of Fe is 11.8%, and the mass percentage of Cr is 10.9%.
[0065] (4) Catalyst evaluation conditions: 15 g of dimethyl maleate was added to a 100 mL stainless steel high-pressure hydrogenation reactor, 0.3 g of Ni2-Fe1-Cr1-Al2O3 catalyst with a 40 mesh screen and 40 mL of anhydrous methanol solvent. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 2 MPa with pure H2. The reaction temperature and pressure were set at 70 °C and 2 MPa, and the reaction was continued at a stirring rate of 600 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 min and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 5.
[0066] Table 5 Evaluation results of catalyst 5
[0067] Catalyst 5 Running time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni2-Fe1-Cr1-Al2O3]]> 80 100 100
[0068] Example 6
[0069] (1) Weigh 11.0 g of nickel nitrate hexahydrate (0.0375 mol), 5.6 g of ferric nitrate nonahydrate (0.01875 mol) and 7.2 g of aluminum nitrate nonahydrate (0.01875 mol) respectively, dissolve them in 190 mL of deionized water, stir at a stirring rate of 500 r / min for 2 h to mix evenly, and obtain a metal salt solution (the total concentration of the metal salt solution is 0.4 mol / L, and the molar fraction ratio of the nickel salt, the iron salt and the aluminum salt is 2:1:1); weigh 7.8 g of NaOH and 8.0 g of Na2CO3 was dissolved in 150mL of deionized water, stirred at a stirring rate of 500r / min for 2h to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.38:1); the temperature of the 190mL deionized water bottom liquid was raised to 95°C, and stirred at a stirring rate of 600r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 1.9:1.5 for coprecipitation titration, and the pH value of the mixed solution was maintained at 11, and the titration was completed in 3.8 hours. After the precipitation was completed, the precipitation solution was stirred at 30°C at a stirring rate of 660r / min for 24 hours for aging to obtain a precursor precipitate.
[0070] (2) Wash the precursor precipitate with deionized water for 4 times until it is neutral; place it in an oven and dry it at 90°C for 12 hours; transfer it to a muffle furnace and calcine it at 500°C in flowing air for 4 hours at a heating rate of 8°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni2Fe1Al-LDHs.
[0071] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:0, the metal oxide Ni2Fe1Al-LDHs was reduced from room temperature to 600°C for 3 hours, and then taken out after cooling to room temperature to obtain catalyst 6, named Ni2-Fe1-Al2O3. The mass percentage of Ni in the obtained catalyst is 36.3%, and the mass percentage of Fe is 17.3%.
[0072] (4) Catalyst evaluation conditions: 10 g of dimethyl maleate was added to a 100 mL stainless steel high-pressure hydrogenation reactor, 0.2 g of Ni2-Fe1-Al2O3 catalyst and 70 mL of anhydrous methanol solvent were screened at 20 mesh. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 3 MPa with pure H2. The reaction temperature and pressure were set at 100 °C and 3 MPa, and the reaction was continued at a stirring rate of 600 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 min and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 6.
[0073] Table 6 Evaluation results of catalyst 6
[0074] Catalyst 6 Running time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni2-Fe1-Al2O3]]> 60 100 100
[0075] Example 7
[0076] (1) Weigh 7.4 g of nickel nitrate hexahydrate (0.025 mol), 6.0 g of copper nitrate trihydrate (0.025 mol) and 9.4 g of aluminum nitrate nonahydrate (0.025 mol) respectively, dissolve them in 100 mL of deionized water, stir at a stirring rate of 600 r / min for 4 h to obtain a metal salt solution (the total concentration of the metal salt solution is 0.75 mol / L, and the molar fraction ratio of the nickel salt, copper salt and aluminum salt is 1:1:1); weigh 4.8 g of NaOH and 3.8 g of Na2CO3 was dissolved in 80mL of deionized water, and stirred at a stirring rate of 600r / min for 4h to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.3:1); the temperature of the 100mL deionized water bottom liquid was raised to 65°C, and stirred at a stirring rate of 540r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 1:0.8 for coprecipitation titration, and the pH value of the mixed solution was maintained at 10, and the titration was completed in 4.4 hours. After the precipitation was completed, the precipitation solution was stirred at 28°C at a stirring rate of 800r / min for 12 hours for aging to obtain a precursor precipitate.
[0077] (2) Wash the precursor precipitate with deionized water for 6 times until it becomes neutral; place it in an oven and dry it at 100°C for 12 hours; transfer it to a muffle furnace and calcine it at 450°C in flowing air for 4 hours at a heating rate of 2°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni1Cu1Al-LDHs.
[0078] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:3, the metal oxide Ni1Cu1Al-LDHs was reduced by heating the temperature from room temperature to 550°C for 3 hours, and then cooled to room temperature and taken out to obtain catalyst 7, named Ni1-Cu1-Al2O3. The mass percentage of Ni in the obtained catalyst was 22.9%, and the mass percentage of Cu was 24.8%.
[0079] (4) Catalyst evaluation conditions: 3 g of dimethyl maleate was added to a 100 mL stainless steel high-pressure hydrogenation reactor, 0.06 g of Ni1-Cu1-Al2O3 catalyst with a 30 mesh screen and 27 mL of anhydrous methanol solvent. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 2 MPa with pure H2. The reaction temperature and pressure were set at 50 °C and 2 MPa, and the reaction was continued at a stirring rate of 600 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 7.
[0080] Table 7 Evaluation results of catalyst 7
[0081] Catalyst 7 Running time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni1-Cu1-Al2O3]]> 80 100 100
[0082] Example 8
[0083] (1) 9.4 g of nickel nitrate hexahydrate (0.0321 mol), 5.2 g of copper nitrate trihydrate (0.0214 mol) and 8.2 g of aluminum nitrate nonahydrate (0.0214 mol) were weighed and dissolved in 115 mL of deionized water, and stirred at a stirring rate of 550 r / min for 35 min to obtain a metal salt solution (the total concentration of the metal salt solution was 0.65 mol / L, and the molar fraction ratio of the nickel salt, copper salt and aluminum salt was 1.5:1:1); 6.0 g of NaOH and 4.8 g of Na2CO3 was dissolved in 100mL of deionized water, and stirred at a stirring rate of 550r / min for 3h to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.3:1); the temperature of the 115mL deionized water bottom liquid was raised to 65°C, and stirred at a stirring rate of 560r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 1.15:1 for coprecipitation titration, and the pH value of the mixed solution was maintained at 10, and the titration was completed in 1.6 hours. After the precipitation was completed, the precipitation solution was stirred at 30°C at a stirring rate of 660r / min for 36 hours for aging to obtain a precursor precipitate.
[0084] (2) Wash the precursor precipitate with deionized water for 4 times until it is neutral; place it in an oven at 95°C for 12 hours; transfer it to a muffle furnace and calcine it at 480°C in flowing air for 4 hours at a heating rate of 5°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni 1.5 Cu1Al-LDHs.
[0085] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:2, the metal oxide Ni 1.5 Cu1Al-LDHs was reduced by heating the temperature from room temperature to 400 °C for 5 hours, and then cooled to room temperature and taken out to obtain catalyst 8, named Ni 1.5 -Cu1-Al2O3. The mass percentage of Ni in the obtained catalyst is 30.0%, and the mass percentage of Cu is 21.6%.
[0086] (4) Catalyst evaluation conditions: 5 g of dimethyl maleate was added to a 100 mL stainless steel high pressure hydrogenation reactor, and 0.1 g of Ni was screened at 30 mesh. 1.5-Cu1-Al2O3 catalyst and 45mL anhydrous methanol solvent. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 2MPa with pure H2. The reaction temperature and pressure were set at 70°C and 2MPa, and the reaction was continued at a stirring rate of 600r / min. During the reaction, a small amount of reaction material was removed through the sampling port every 5min and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated, and the evaluation results are shown in Table 8.
[0087] Table 8 Evaluation results of catalyst 8
[0088] Catalyst 8 Running time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni 1.5 -Cu1-Al2O3]]> 75 100 100
[0089] Example 9
[0090] (1) Weigh 11.3 g of nickel nitrate hexahydrate (0.0375 mol), 4.5 g of copper nitrate trihydrate (0.01875 mol) and 7.1 g of aluminum nitrate nonahydrate (0.01875 mol) respectively, dissolve them in 125 mL of deionized water, stir at a stirring rate of 500 r / min for 2.5 h to mix evenly, and obtain a metal salt solution (the total concentration of the metal salt solution is 0.6 mol / L, and the molar fraction ratio of the nickel salt, copper salt and aluminum salt is 2:1:1); weigh 6.0 g of NaOH and 4.8 g of Na2CO3 was dissolved in 100mL of deionized water, stirred at a stirring rate of 500r / min for 2.5h to mix evenly, and a NaOH-Na2CO3 mixed alkaline solution (nNa2CO3:nNaOH=0.3:1) was obtained; the temperature of the 125mL deionized water bottom liquid was raised to 65°C, and stirred at a stirring rate of 600r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkaline solution was controlled to be 1.25:1 for coprecipitation titration, and the pH value of the mixed solution was maintained at 11, and the titration was completed in 5.7 hours. After the precipitation was completed, the precipitation solution was stirred at 20°C at a stirring rate of 660r / min for 24 hours for aging to obtain a precursor precipitate.
[0091] (2) Wash the precursor precipitate with deionized water for 5 times until it is neutral; place it in an oven and dry it at 90°C for 12 hours; transfer it to a muffle furnace and calcine it at 600°C in static air for 3 hours at a heating rate of 10°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni2Cu1Al-LDHs.
[0092] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:0.5, the metal oxide Ni2Cu1Al-LDHs was reduced from room temperature to 600°C for 3 hours, and then taken out after cooling to room temperature to obtain catalyst 9, named Ni2-Cu1-Al2O3. The mass percentage of Ni in the obtained catalyst is 35.5%, and the mass percentage of Cu is 19.2%.
[0093] (4) Catalyst evaluation conditions: 10 g of dimethyl maleate was added to a 100 mL stainless steel high-pressure hydrogenation reactor, 0.2 g of Ni2-Cu1-Al2O3 catalyst with a 60 mesh screen and 70 mL of anhydrous methanol solvent. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 5 MPa with pure H2. The reaction temperature and pressure were set at 120 °C and 5 MPa, and the reaction was continued at a stirring rate of 500 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 9.
[0094] Table 9 Evaluation results of catalyst 9
[0095] Catalyst 9 Running time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni2-Cu1-Al2O3]]> 60 100 100
[0096] Example 10
[0097] (1) Weigh 13.1 g of nickel nitrate hexahydrate (0.045 mol), 4.4 g of cobalt nitrate hexahydrate (0.015 mol) and 5.6 g of aluminum nitrate nonahydrate (0.015 mol) respectively, dissolve them in 75 mL of deionized water, stir at a stirring rate of 500 r / min for 6 h to obtain a metal salt solution (the total concentration of the metal salt solution is 1 mol / L, and the molar fraction ratio of the nickel salt, cobalt salt and aluminum salt is 3:1:1); weigh 2.6 g of NaOH and 2.7 g of Na2CO3 was dissolved in 50mL of deionized water, and stirred at a stirring rate of 500r / min for 6h to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.38:1); the temperature of the 75mL deionized water bottom liquid was raised to 65°C, and stirred at a stirring rate of 500r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 0.75:0.5 for coprecipitation titration, and the pH value of the mixed solution was maintained at 9, and the titration was completed in 6 hours. After the precipitation was completed, the precipitation solution was stirred at 30°C at a stirring rate of 660r / min for 36 hours for aging to obtain a precursor precipitate.
[0098] (2) Wash the precursor precipitate with deionized water for 4 times until it becomes neutral; place it in an oven and dry it at 200°C for 12 hours; transfer it to a muffle furnace and calcine it at 500°C in flowing air for 4 hours at a heating rate of 8°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni3Co1Al-LDHs.
[0099] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:3, the metal oxide Ni3Co1Al-LDHs was reduced from room temperature to 400°C for 5 hours, and then taken out after cooling to room temperature to obtain catalyst 10, named Ni3-Co1-Al2O3. The mass percentage of Ni in the obtained catalyst is 43.9%, and the mass percentage of Co is 14.7%.
[0100] (4) Catalyst evaluation conditions: 3 g of dimethyl maleate was added to a 100 mL stainless steel high-pressure hydrogenation reactor, 0.06 g of Ni3-Co1-Al2O3 catalyst and 27 mL of anhydrous methanol solvent were screened with 30 mesh. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 2 MPa with pure H2. The reaction temperature and pressure were set at 50 °C and 2 MPa, and the reaction was continued at a stirring rate of 600 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 10.
[0101] Table 10 Evaluation results of catalyst 10
[0102] Catalyst 10 Operation time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni3-Co1-Al2O3]]> 30 100 100
[0103] Embodiment 11
[0104] (1) 8.7 g of nickel nitrate hexahydrate (0.03 mol), 4.4 g of cobalt nitrate hexahydrate (0.015 mol), 3.6 g of copper nitrate trihydrate (0.015 mol) and 5.6 g of aluminum nitrate nonahydrate (0.015 mol) were weighed and dissolved in 75 mL of deionized water, and stirred at a stirring rate of 500 r / min for 6 h to obtain a metal salt solution (the total concentration of the metal salt solution was 1 mol / L, and the molar fraction ratio of the nickel salt, cobalt salt, copper salt and aluminum salt was 2:1:1:1); 2.6 g of NaOH and 2.7 g of Na2CO3 was dissolved in 50mL of deionized water, and stirred at a stirring rate of 500r / min for 6h to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.38:1); the temperature of the 75mL deionized water bottom liquid was raised to 65°C, and stirred at a stirring rate of 500r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 0.75:0.5 for coprecipitation titration, and the pH value of the mixed solution was maintained at 9, and the titration was completed in 6 hours. After the precipitation was completed, the precipitation solution was stirred at 25°C at a stirring rate of 660r / min for 36 hours for aging to obtain a precursor precipitate.
[0105] (2) Wash the precursor precipitate with deionized water for 4 times until it becomes neutral; place it in an oven and dry it at 200°C for 12 hours; transfer it to a muffle furnace and calcine it at 500°C in flowing air for 4 hours at a heating rate of 8°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni2Co1Cu1Al-LDHs.
[0106] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:2.5, the metal oxide Ni2Co1Cu1Al-LDHs was reduced from room temperature to 400°C for 5 hours, and then taken out after cooling to room temperature to obtain catalyst 11, named Ni2-Co1-Cu1-Al2O3. The mass percentage of Ni in the obtained catalyst is 28.9%, the mass percentage of Co is 14.5%, and the mass percentage of Cu is 15.7%.
[0107] (4) Catalyst evaluation conditions: 3 g of dimethyl maleate was added to a 100 mL stainless steel high-pressure hydrogenation reactor, 0.06 g of Ni2-Co1-Cu1-Al2O3 catalyst with a 30 mesh screen and 27 mL of anhydrous methanol solvent. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 5 MPa with pure H2. The reaction temperature and pressure were set at 120 °C and 5 MPa, and the reaction was continued at a stirring rate of 600 r / min. During the reaction, a small amount of reaction material was removed from the sampling port every 5 min and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 11.
[0108] Table 11 Evaluation results of catalyst 11
[0109] Catalyst 11 Operation time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni2-Co1-Cu1-Al2O3]]> 30 100 100
[0110] Example 12
[0111] (1) Weigh 10.9 g of nickel nitrate hexahydrate (0.0375 mol), 7.5 g of chromium nitrate nonahydrate (0.01875 mol) and 7.0 g of aluminum nitrate nonahydrate (0.01875 mol) respectively, dissolve them in 190 mL of deionized water, stir at a stirring rate of 550 r / min for 50 min to mix evenly, and obtain a metal salt solution (the total concentration of the metal salt solution is 0.4 mol / L, and the molar fraction ratio of the nickel salt, chromium salt and aluminum salt is 2:1:1); weigh 6.8 g of NaOH and 5.5 g of Na2CO3 was dissolved in 170mL of deionized water, and stirred at a stirring rate of 550r / min for 50min to obtain a NaOH-Na2CO3 mixed alkali solution (nNa2CO3:nNaOH=0.3:1); the temperature of the 190mL deionized water bottom liquid was raised to 60°C, and stirred at a stirring rate of 560r / min; the volume flow ratio of the metal salt solution and the NaOH-Na2CO3 mixed alkali solution was controlled to be 1.9:1.7 for coprecipitation titration, and the pH value of the mixed solution was maintained at 10, and the titration was completed in 1.6 hours. After the precipitation was completed, the precipitation solution was stirred at 30°C at a stirring rate of 660r / min for 12 hours for aging to obtain a precursor precipitate.
[0112] (2) Wash the precursor precipitate with deionized water for 4 times until it becomes neutral; place it in an oven at 95°C for 12 hours; transfer it to a muffle furnace and calcine it at 480°C in flowing air for 4 hours at a heating rate of 5°C / min. After cooling to room temperature, take it out to obtain the metal oxide Ni2Cr1Al-LDHs.
[0113] (3) In a hydrogen / nitrogen atmosphere with a volume flow ratio of 1:3, the metal oxide Ni2Cr1Al-LDHs was reduced from room temperature to 400°C for 5 hours, and then taken out after cooling to room temperature to obtain catalyst 12, named Ni2-Cr1-Al2O3. The mass percentage of Ni in the obtained catalyst is 29.1%, and the mass percentage of Cr is 12.9%.
[0114] (4) Catalyst evaluation conditions: 5 g of dimethyl maleate was added to a 100 mL stainless steel high-pressure hydrogenation reactor, 0.1 g of Ni2-Cr1-Al2O3 catalyst and 45 mL of anhydrous methanol solvent were screened at 30 mesh. After sealing, the reaction system was first flushed with N2 and H2 5 times each, and then pressurized to 1 MPa with pure H2. The reaction temperature and pressure were set at 70 °C and 1 MPa, and the reaction was continued at a stirring rate of 600 r / min. During the reaction, a small amount of reaction material was removed through the sampling port every 5 minutes and its composition was analyzed. The product after the reaction was analyzed by gas chromatograph (Aglient 7890A), and the content of each component was detected by hydrogen ion flame detector (FID), and its capillary column was HP-5. The conversion rate of the reaction substrate and the selectivity of the product were calculated. The evaluation results are shown in Table 12.
[0115] Table 12 Evaluation results of catalyst 12
[0116]
[0117] Comparative Example 1
[0118] Without adding the second metal element, only 14.5 g of nickel nitrate hexahydrate and 9.4 g of aluminum nitrate nonahydrate were weighed, and the other preparation steps were the same as those in Example 3 to obtain a comparative catalyst 1, named Ni2 / Al2O3.
[0119] The catalyst evaluation conditions were the same as those in Example 3. The evaluation results are shown in Table 13.
[0120] Table 13 Comparative evaluation results of catalyst 1
[0121] Comparative Catalyst 1 Operation time / min DMM conversion rate / % DMS selectivity / % <![CDATA[Ni2 / Al2O3]]> 80 85 95
[0122] Comparative Example 2
[0123] The catalyst was prepared by equal volume impregnation method. 6.62 g of nickel nitrate hexahydrate and 2.36 g of cobalt nitrate hexahydrate were weighed, dissolved in 2 mL of deionized water, and added dropwise to 2.0 g of Al2O3 carrier powder for equal volume impregnation. The subsequent treatment was consistent with Example 3 to obtain comparative catalyst 2, named NiCo / Al2O3-IMP.
[0124] The catalyst evaluation conditions were the same as those in Example 3. The evaluation results are shown in Table 14.
[0125] Table 14 Comparative evaluation results of catalyst 2
[0126] Comparative Catalyst 2 Operation time / min DMM conversion rate / % DMS selectivity / % <![CDATA[NiCo / Al2O3-IMP]]> 100 75 90
[0127] The active metal content and texture and structural parameters of the Ni-M bimetallic multifunctional catalysts prepared in Examples 1 to 12 and the catalysts prepared in Comparative Examples 1 and 2 are shown in Table 15.
[0128] Table 15 Active metal content and texture and structural parameters of catalysts 1 to 12 and comparative catalysts 1 and 2
[0129]
[0130] Characterization Test
[0131] (1) XRD characterization
[0132] XRD test was performed on the calcined and reduced samples of the precursor of Example 3 of the present invention and the reduced sample of Comparative Example 1. The test results are as follows: Figure 1 As shown in the figure, after calcination at 500°C, the collapse of the layered structure of Example 3 caused the characteristic diffraction peak of LDH to disappear, and it existed in the form of metal oxides, forming NiAl2O4 and Co2AlO4 spinel species. After H2 reduction, the diffraction peak of the hydrotalcite in Comparative Example 1 disappeared, and characteristic diffraction peaks appeared at 44.3°, 51.9°, and 76.8°. These diffraction peaks correspond to the (111), (200), and (220) crystal planes of Ni. In Example 3, new Ni x Co y This is because the addition of Co species will cause defect sites in metallic Ni, resulting in the formation of a uniform Ni-Co metal alloy inside or on the inner surface of the Al2O3 framework.
[0133] (2) BET characterization
[0134] The calcined sample of Example 6 of the present invention was subjected to a BET test. The test results are as follows: Figure 2 As shown in the figure, Example 6 presents a typical IV type isotherm and has an obvious hysteresis loop, indicating that a good mesoporous structure is formed during the calcination process; from the pore size distribution diagram, it can be seen that the pore size distribution is around 5 nm.
[0135] (3) H2 temperature-programmed reduction characterization
[0136] The samples of Example 3 and Comparative Example 1 were subjected to H2-programmed temperature reduction test. The test results are as follows: Figure 3As shown. It can be seen from the figure that Comparative Example 1 has two obvious H2 reduction signal peaks, and the corresponding central temperatures are 325°C and 500°C, respectively. The reduction peak at low temperature (325°C) comes from the reduction of the Ni component with weak interaction with the carrier, while the reduction peak at high temperature (500°C) corresponds to the reduction of the Ni component with strong interaction with the carrier. Example 3 has two obvious reduction signal peaks, and the corresponding central temperatures are 285°C and 585°C, respectively. The main reduction peak moves to a slightly higher temperature (585°C), which can be attributed to the formation of NiCo alloy. The formation of NiCo alloy can enhance the interaction with the carrier and increase the reduction temperature of Ni. A wide low-temperature peak is also observed in the temperature range of 200 to 300°C, which may be due to the partial reduction of a small amount of cobalt oxide phase.
[0137] The above description is only for better explaining the embodiments of the present invention, and is not intended to limit the present invention. Any modification or equivalent substitution that does not depart from the spirit and scope of the present invention shall fall within the scope of the present invention.
Claims
1. A Ni-based bimetallic multifunctional catalyst, characterized in that: The general formula of the Ni-based bimetallic multifunctional catalyst is Ni-M-Al2O3, wherein M represents one to three of Cr, Mn, Fe, Co or Cu; Al2O3 is used as a carrier, Ni and M are metal active components, the microstructure of the carrier Al2O3 exists in an amorphous form, and a partial lamellar skeleton structure of hydrotalcite is maintained at the nanoscale, and nanoparticles of the metal active components Ni and M are uniformly distributed inside or on the inner surface of the Al2O3 skeleton, that is, Ni-M alloy nanoparticles are uniformly grown on the lamellar pore walls of the Al2O3 nanosheets.
2. The Ni-based bimetallic multifunctional catalyst according to claim 1, characterized in that: In terms of mass percentage, the contents of the components in the Ni-M-Al2O3 are as follows: Ni is 20-50%, M is 10-30%, and the total amount of Ni+M is 20-60%, with the remainder being Al2O3.
3. The Ni-based bimetallic multifunctional catalyst according to claim 2, characterized in that: The specific surface area of Ni-M-Al2O3 is 140-180m 2 ·g -1 The average pore size is 5-15 nm and the pore volume is 0.25-0.65 cm 3 ·g -1 , the Ni-M alloy particle size is 3.5~9.5nm.
4. The method for preparing the Ni-based bimetallic multifunctional catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dissolving nickel salt, M salt and aluminum salt in deionized water to prepare a metal salt solution; dissolving NaOH and Na2CO3 in deionized water to prepare a NaOH-Na2CO3 mixed alkaline solution; (2) adding NaOH-Na2CO3 mixed alkali solution and metal salt solution to deionized water simultaneously for coprecipitation titration; (3) After the co-precipitation is completed, the precipitation solution is aged to obtain a precursor precipitate; (4) washing, drying, and calcining the precursor precipitate to obtain metal oxide NiMAl-LDHs; (5) The metal oxide NiMAl-LDHs is reduced to obtain the catalyst Ni-M-Al2O3.
5. The method for preparing the Ni-based bimetallic multifunctional catalyst according to claim 4, characterized in that: In the step (1), the nickel salt, M salt and aluminum salt are solutions of their nitrates, acetates or other soluble salts; the molar fraction ratio of the nickel salt, M salt and aluminum salt is 1-3:1-3:1, and the molar fraction ratio of the nickel salt + M salt and aluminum salt is 2-4:1; the total concentration of the metal salt solution is 0.3-1.0 mol / L, and the volume of the metal salt solution is 75-250 mL; the concentration of NaOH in the NaOH-Na2CO3 mixed alkaline solution is 1-1.8 mol / L, the concentration of Na2CO3 is 0.3-0.6 mol / L, and the molar ratio of NaOH to Na2CO3 is 0.3-0.38:1; the volume of the NaOH-Na2CO3 mixed alkaline solution is 50-200 mL.
6. The method for preparing the Ni-based bimetallic multifunctional catalyst according to claim 4, characterized in that: The volume of deionized water in step (2) is 75 to 250 mL; during the coprecipitation titration process, the volume flow ratio of the metal salt solution to the NaOH-Na2CO3 mixed alkaline solution is controlled to be 0.75 to 2.5:0.5 to 2, the titration duration is 1.3 to 6 hours, the pH value of the mixed solution is maintained at 9 to 11, and the operating temperature is 50 to 100°C.
7. The method for preparing the Ni-based bimetallic multifunctional catalyst according to claim 4, characterized in that: The aging temperature in step (3) is 20-30°C and the time is 12-36 hours; the washing liquid used for washing in step (4) is deionized water, ethanol or ethanol / water mixed solution, and the drying temperature is 70-200°C.
8. The method for preparing the Ni-based bimetallic multifunctional catalyst according to claim 4, characterized in that: The calcination conditions in step (4) are as follows: the calcination atmosphere is static air, flowing air or flowing nitrogen atmosphere, the heating rate is 0.5-10°C / min, the calcination temperature is 350-600°C, and the calcination time is 3-6h.
9. The method for preparing the Ni-based bimetallic multifunctional catalyst according to claim 4, characterized in that: The reduction conditions in step (5) are as follows: the reducing gas is hydrogen or a mixture of hydrogen and nitrogen, wherein the volume flow ratio of hydrogen to nitrogen is 1:0-3, the reduction temperature is 400-600° C., and the reduction time is 3-5 hours.
10. The use of the Ni-based bimetallic multifunctional catalyst according to any one of claims 1 to 3, characterized in that: Used for hydrogenation of dimethyl maleate to produce dimethyl succinate.
Citation Information
Patent Citations
Method for preparing hydrogenation catalyst for producing dimethyl succinate
CN103464153A
System and method for preparing dimethyl succinate through liquid phase hydrogenation of dimethyl maleate
CN115253923A
Cited By
Fe-Cu-Mn ternary hydrotalcite-like catalyst and preparation method thereof
CN121551040A
Five-element co-doped porous CoFeCuMnNi-LDH nano material as well as preparation method and application thereof
CN121819864A